Access to Care for Homeless Veterans During Disasters - Alicia R. Gable; Claudia Der-Martirosian; Aram Dobalian (SAGE Publishing, 2018)
Introduction: Since 1970, natural disasters have led to both temporary and permanent closures of multiple medical centers and outpatient clinics at the US Department of Veterans Affairs (VA) nationwide. Access to care during such events is critical for vulnerable populations, especially homeless veterans. As such, facility closures may disproportionately affect homeless veteran patients who are both more likely to experience adverse effects from disasters and face multiple barriers to care. Methods: A cross-sectional survey was administered to a probability sample of 2000 homeless VA patients living in and receiving VA health care in the Northeast United States. The survey was completed by 383 respondents (20% adjusted response rate). This pilot study examines predictors of difficulty accessing care in the event that the VA facility that homeless VA patients routinely use is forced to close because of a natural disaster. Results: In a multivariate logistic regression, homeless VA patients who had Medicaid were less likely (OR 0.38; 95% CI: 0.18-0.78; P < .01) to report that they would have difficulty obtaining care elsewhere if their normal VA facility was closed in a future natural disaster. Conclusions: Findings suggest that Medicaid coverage has the potential to facilitate access to care for homeless veteran VA patients during disasters. Policy changes that decrease Medicaid coverage could limit access to care for homeless veterans during closures of VA medical facilities.